2022
DOI: 10.3390/s22072537
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Functional Connectivity during the Sensorimotor Integration Detected by Artificial Neural Network

Abstract: Large-scale functional connectivity is an important indicator of the brain’s normal functioning. The abnormalities in the connectivity pattern can be used as a diagnostic tool to detect various neurological disorders. The present paper describes the functional connectivity assessment based on artificial intelligence to reveal age-related changes in neural response in a simple motor execution task. Twenty subjects of two age groups performed repetitive motor tasks on command, while the whole-scalp EEG was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Moreover, although task complexity effect was more robust for the auditory than visual modality in the two age groups, the altered connectivity of the movement-generating M1 in aged subjects was not affected by this interaction. Together, these observations support and extend previous studies (Frolov et al 2020;Rosjat et al, 2021;Pitsik et al, 2022) by revealing that the detected effects of aging on contra-lateral M1 connections are stable, not being modulated by functional variables and task processing demands.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, although task complexity effect was more robust for the auditory than visual modality in the two age groups, the altered connectivity of the movement-generating M1 in aged subjects was not affected by this interaction. Together, these observations support and extend previous studies (Frolov et al 2020;Rosjat et al, 2021;Pitsik et al, 2022) by revealing that the detected effects of aging on contra-lateral M1 connections are stable, not being modulated by functional variables and task processing demands.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, when processes of external sensory guidance or motor planning, initiation, and sensorimotor integration are considered, networks from slower frequency bands appear to be functionally reactive. Rosjat et al (2018Rosjat et al ( , 2021 have identified age differences for a lowfrequency (delta/theta) network characterized by reduced variability of the subnetworks, emergence of additional enhanced inter-hemispheric connections, and different activations of prefrontal and premotor areas (see Frolov et al, 2020, Pitsik et al, 2022 for similar results). These low-frequency networks appear of special interest also because response-related potentials (RRPs) generated after external sensory stimulation are composed of slower frequency components from delta/theta frequency bands in both young and old individuals (Popovych et al, 2016;Liu et al, 2017;Yordanova et al, 2004Yordanova et al, , 2020.…”
Section: Introductionmentioning
confidence: 92%
“…In this context, Dushanova and Christov [ 15 ] found the age-related distinctions in low-frequency EEG activity, which more likely indicate a decrease in memory operations during sensory processing in elderly adults. Our recent study identified an age-related deficit of working memory as a potential factor in the slowing of auditory-stimulated motor execution [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%